Dampak Psikologis pada Pekerja Seks Waria di Kawasan Sawerigading, Makassar - Alfa Caesar De Alexio Kase; Sriwahyuni Sriwahyuni; Muh. Reski Salemuddin; Muh Indrabudiman; Hasanudin Kasim (Yayasan Literasi Sains Indonesia, 2025)
Transgender sex workers often experience discrimination, social stigma, psychological pressure, and limited access to employment, education, and legal protection. Therefore, this study aims to reveal the psychological impacts on transgender sex workers, based on interviews with four informants in the Sawerigading area of Makassar City, selected through purposive sampling. This research employs a qualitative case study approach using interviews and observations to understand the psychological impacts in a deep and contextual manner. Data were analyzed thematically through data reduction, data display, and conclusion drawing. The findings show that transgender sex workers in Sawerigading experience psychological pressure due to stigma, discrimination, and economic demands. The conflict between self-acceptance and social rejection generates stress, anxiety, and the use of defense mechanisms. The lack of social support worsens their mental condition, indicating the need for serious attention to create a fair, inclusive, and humane environment. Therefore, it is crucial to improve access to mental health services, public education to reduce stigma, strengthen social support, and develop inclusive policies that protect the rights and dignity of transgender individuals.